2021
DOI: 10.1038/s41586-021-03969-3
|View full text |Cite
|
Sign up to set email alerts
|

Isoform cell-type specificity in the mouse primary motor cortex

Abstract: Full-length SMART-seq1 single-cell RNA sequencing can be used to measure gene expression at isoform resolution, making possible the identification of specific isoform markers for different cell types. Used in conjunction with spatial RNA capture and gene-tagging methods, this enables the inference of spatially resolved isoform expression for different cell types. Here, in a comprehensive analysis of 6,160 mouse primary motor cortex cells assayed with SMART-seq, 280,327 cells assayed with MERFISH2 and 94,162 ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 67 publications
10
100
0
Order By: Relevance
“…To date, several studies demonstrated that single-cell RNA-seq has provided valuable insights into cell-type-specific AS events ( Li et al, 2015 ; Zhang et al, 2016 ; Karlsson and Linnarsson, 2017 ; Gupta et al, 2018 ; Booeshaghi et al, 2021 ). However, our single-cell AS analysis showed that most AS events were not cell-type-specific except for a few cases and revealed tremendous AS event varieties in ependymal quiescent neural stem cells, activated neural stem cells, and neuroblast cells ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies demonstrated that single-cell RNA-seq has provided valuable insights into cell-type-specific AS events ( Li et al, 2015 ; Zhang et al, 2016 ; Karlsson and Linnarsson, 2017 ; Gupta et al, 2018 ; Booeshaghi et al, 2021 ). However, our single-cell AS analysis showed that most AS events were not cell-type-specific except for a few cases and revealed tremendous AS event varieties in ependymal quiescent neural stem cells, activated neural stem cells, and neuroblast cells ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent such a problem, single-cell-based alternative splicing analyses become imperative. By single-cell RNA sequencing, researchers identified cell-type-specific mRNA isoforms in the mouse primary motor cortex and cerebellum ( Gupta et al, 2018 ; Booeshaghi et al, 2021 ) and mRNA isoform diversity of oligodendrocyte and vascular and leptomeningeal cells in the mouse brain ( Karlsson and Linnarsson, 2017 ), and found splicing dynamics during the differentiation of human iPSCs to motor neurons or neuron progenitor cells ( Song et al, 2017 ). At present, few research efforts have been dedicated to AS studies in a single cell at neurogenic regions.…”
Section: Introductionmentioning
confidence: 99%
“…s3-us-west-2.amazonaws.com/Data-objects/tabula-muris-senis-facs-processed-official-annotations.h5ad (filtering details in (Tabula Muris Consortium, 2020)). BICCN Cortex data (Yao et al, 2021) were downloaded from https://assets.nemoarchive.org/dat-ch1nqb7 and filtered as in (Booeshaghi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This observation comports with previous findings that the mammalian brain has exceptionally high levels of alternative splicing (Yeo et al, 2004). Booeshaghi et al (2021) analyzed BICCN Cortex at the transcript level, but focused on changes in absolute transcript expression rather than proportions. While the authors indirectly find some differences in transcript proportions by inspecting genes with no differential expression, this is not a systematic analysis of differential transcript usage.…”
Section: Augmenting Cell Atlases With Splicing Informationmentioning
confidence: 99%
“…The binary model is not large enough to include the diversity of possible splicing dynamics, but approximately holds under fairly restrictive conditions: the predominance of a single terminal isoform, as well as the existence of a single rate-limiting step in the splicing process. Previous work reports that minor isoforms are non-negligible [67,69], differential isoform expression is physiologically significant [69][70][71], and intron retention in particular is implicated in regulation and pathology [72][73][74][75].…”
Section: Pre-processingmentioning
confidence: 99%